Boston Riots Three Centuries of Social Violence - Tager, Jack (Northeastern University Press, 2019)
From the food uprisings in the early 1700s to the notorious anti-busing riots in the mid-1970s, incidents of communal social violence have played a significant role in Boston's history. This vivid portrait of an ever-changing community over time provides a revealing glimpse into peoples' anger, aspirations, and frustrations. It sheds new light on why groups are provoked to take unlawful action in response to unjust conditions, and it opens a fresh vista on the social history of Boston. Originally published by Northeastern University Press in 2001. With a new foreword by Gordana Rabrenovic.